PEMBINAAN ANAK DIDIK PEMASYARAKATAN BERORIENTASI REHABILITASI SOSIAL DI LEMBAGA PEMASYARAKATAN KELAS IIB MERAUKE - Mulyadi Alrianto Tajuddin; leonardus Abung (Al-Adalah: Jurnal Hukum dan Politik Islam, 2019)
The effectiveness in the existence of social rehabilitation for correctional students in Merauke Class IIB Correctional Institutions has not yet fully provided guidance in accordance with Law Number 12 of 1995 concerning Corrections because the Class IIB Correctional Institution of Merauke is a General Correctional Institution and Not a Special Penitentiary for Children. This study examines the formation of correctional students in Merauke Class IIB Correctional Institutions which are socially oriented and inhibiting factors in conducting social rehabilitation for correctional students in the Class IIB Correctional Institution of Merauke. This study uses an empirical juridical approach method with a qualitative analysis which then results are obtained that the social rehabilitation of the implementation of coaching in the Class IIB Correctional Institution of Merauke is carried out namely the fostering of religious awareness, fostering intellectual abilities (intelligence) and fostering legal awareness, However, social rehabilitation such as fostering national and state awareness, and guidance to interact with the community has not been carried out at the Merauke Class IIB Penitentiary so that social rehabilitation at the Merauke Class IIB Penitentiary has not been effective and there is also a lack of facilities and staff resources at the Class IIB Penitentiary Office in Merauke. There needs to be an increase in solutions to solutions or alternatives in the completion of social rehabilitation in the future will be achieved and carried out properly referring to Law No. 12 of 1995 concerning Corrections